2022
DOI: 10.3389/fendo.2022.900356
|View full text |Cite
|
Sign up to set email alerts
|

Finite Element Analysis of Osteoporotic and Osteoblastic Vertebrae and Its Association With the Proton Density Fat Fraction From Chemical Shift Encoding-Based Water-Fat MRI – A Preliminary Study

Abstract: PurposeOsteoporosis is prevalent and entails alterations of vertebral bone and marrow. Yet, the spine is also a common site of metastatic spread. Parameters that can be non-invasively measured and could capture these alterations are the volumetric bone mineral density (vBMD), proton density fat fraction (PDFF) as an estimate of relative fat content, and failure displacement and load from finite element analysis (FEA) for assessment of bone strength. This study’s purpose was to investigate if osteoporotic and o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 92 publications
0
2
0
Order By: Relevance
“…In the past decade, the important role of PDFF of VBs in bone loss prevention was proposed by a series of studies [ 22 , 23 , 24 ]. According to Schwartz et al’s research [ 25 ], high levels of PDFF are linked to lower BMD and an increased risk of fractures.…”
Section: Discussionmentioning
confidence: 99%
“…In the past decade, the important role of PDFF of VBs in bone loss prevention was proposed by a series of studies [ 22 , 23 , 24 ]. According to Schwartz et al’s research [ 25 ], high levels of PDFF are linked to lower BMD and an increased risk of fractures.…”
Section: Discussionmentioning
confidence: 99%
“…The FE method has been used to simulate the mechanical behavior of bone with increasing fidelity for decades, which has shown great reliability to assess bone strength and fracture risk (8)(9)(10). Previous studies confirmed the superiority of FEA to DXA-aBMD (11) and even QCT-vBMD (12) in both prevalent and incident vertebral fracture prediction (13)(14)(15)(16). Aside from fracture prediction, FEA has a unique value in the opportunistic screening of osteoporosis (7), drug efficacy (17), and postoperative evaluation of internal fixation (18).…”
Section: Introductionmentioning
confidence: 99%